Design and study of the energy-efficient unified apparatuses for energy-technological manufacturing - Nikolsky, Valeriy; Oliynyk, Olga; Ved, Viktor; Svietkina, Olena; Pugach, Andrii; Shvachka, Alexander (Eastern-European Journal of Enterprise Technologies, 2018)
The improved industrial sample of the rotor-pulse heat generator (RPH), integrated into the thermal heating systems of industrial buildings, was produced. Rotor-pulse generators do not occupy significant positions in the market of heating equipment because of the lack of reliable data on effectiveness of the use of such equipment in the thermal heating systems of industrial facilities. The design of the developed cavitation chamber was changed, parameters of the channels, located between the rotor and the stator, were determined. It was found that the optimal width of the gap between the rotor and the stator channels at maximum efficiency of 0.7 was 8–10 mm. When integrating the cavitation chamber of the RPH into the thermal system, the design of the heat exchanger "pipe-in-pipe" was changed into the plate one. Bench tests of energy efficiency of the thermal system operation were conducted. Indicators of energy efficiency of the system with the improved RPH were determined, the analysis was performed by comparing with analogues, described in the literature. It was proved that improvement of the thermal system allowed obtaining the improved indicators of energy efficiency. Bench testing showed that efficiency of the improved thermal system is by ≈17 % higher than efficiency of thermal systems based on the multi-stage RPH. The automatic system of monitoring and control of the thermal system with the use of vibration-frequency sensors for assessment of cavitation process effectiveness was developed. The conducted commissioning works made it possible to determine the possibility of applying the developed automatic system with appropriate software for monitoring and control of the thermal system operation. The obtained data of comparative analysis allow recommending the developed rotor-pulse heat generator as a credible alternative to the used thermal devices in thermal heating systems of industrial buildings.